UN Reform and Its Mandate on International Peace and Security - Bandoro, Bantarto (UI Scholars Hub, 2005)
There was a widespread consensus that the United Nations has to represent the fundamental changes in political world, and Security Council urgently need to be reformed. It is stated that Security Council is obliged to play an active role in international security issues. This following article explained that the spirit of reformation must giving the United Nations an inspiration to recovered its status as a legitimate inter-governmental organizations and possesess stronger and more legitimate mandate on international peace and securty.